The bridge between anxiety and insomnia symptoms among Chinese adults before and after SARS-CoV-2 vaccination: a network analysis - Liu, Yan; Luo, Shangyu; Jiang, Chao; Guo, Jing; Dai, Minhui; Feng, Li; Li, Mingxia; Wen, Jun; Zhang, Xiaobo (Frontiers in Psychiatry, 2025)
BackgroundTo explore the underlying mechanism and changes of anxiety and insomnia before and after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination, we conducted an online cross-sectional survey.MethodsThis is a cross-sectional study conducted in two phases: the first phase was from May to June 2020 (before vaccination) and the second phase was from June to August 2021 (after vaccination). In total, 2245 participants were enrolled before vaccination, and 7207 participants were enrolled after vaccination. Anxiety was measured using the Generalized Anxiety Disorder–7(GAD-7) Scale and insomnia using the Athens Insomnia Scale-8(AIS-8) Scale. Network analysis models were applied to examine the correlation between anxiety and insomnia. Furthermore, a network comparison test was performed to compare network characteristics before and after vaccination.ResultsOur work showed that participants’ anxiety and insomnia scores were lower after vaccination than before vaccination. Sense of well-being during the day (AIS6) in AIS remained high both before and after vaccination. The central intensity of premature wakefulness (AIS3), feeling afraid, and functioning (physical and mental) during the day (AIS7) decreased after vaccination, and the mediation between sense of well-being during the day (AIS6) and sleeping during the day (AIS8) increased significantly.LimitationsThe study was a cross-sectional survey. The numbers of participants differed much in the two groups.ConclusionsThe proportion of participants experiencing anxiety and insomnia decreased significantly after SARS-CoV-2 vaccination. Network analysis identified psychosis-related symptoms as key links between anxiety and insomnia. These findings suggest that targeted interventions focusing on daytime emotional regulation could improve mental health outcomes, guiding healthcare practices during public health crises.